2021
DOI: 10.1016/j.intimp.2021.108125
|View full text |Cite
|
Sign up to set email alerts
|

Increased LPS levels coexist with systemic inflammation and result in monocyte activation in severe COVID-19 patients

Abstract: Mucosal barrier alterations may play a role in the pathogenesis of several diseases, including COVID-19. In this study we evaluate the association between bacterial translocation markers and systemic inflammation at the earliest time-point after hospitalization and at the last 72 h of hospitalization in survivors and non-survivors COVID-19 patients. Sixty-six SARS-CoV-2 RT-PCR positive patients and nine non-COVID-19 pneumonia controls were admitted in this study. Blood samples were collected at hospital admiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…Multiple-fold increases in CCL5 expression in severe COVID-19 patients compared to healthy individuals are well documented ( 311 , 312 , 315 , 324 ). Additionally, there was a significant increase in CCL5 expression in non-surviving COVID-19 patients compared to severe, mild and healthy groups ( 313 ). Furthermore, high levels of CCL5 cause liver disorders and acute kidney injury (AKI) in COVID-19 patients ( 314 , 318 , 325 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple-fold increases in CCL5 expression in severe COVID-19 patients compared to healthy individuals are well documented ( 311 , 312 , 315 , 324 ). Additionally, there was a significant increase in CCL5 expression in non-surviving COVID-19 patients compared to severe, mild and healthy groups ( 313 ). Furthermore, high levels of CCL5 cause liver disorders and acute kidney injury (AKI) in COVID-19 patients ( 314 , 318 , 325 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this module, we also identified several hub-high traffic genes that were crucial in regulating the host immune response during COVID-19. These hub-high traffic genes included CDKN2A (308,309), OASL (282,310), CCL5 (311)(312)(313)(314)(315)(316), KIF2C (4), and CD8A (317). Among them, the CCL5 hub-high traffic gene has the most important role in regulating the inflammatory response and the host immune system; however, its excessive expression can amplify inflammatory responses toward immunopathology (e.g., cytokine storm) (311,314).…”
Section: Midnightblue Modulementioning
confidence: 99%
“…The data were processed using LabSolutions software (Shimadzu). In addition, LPS concentration was determined by quantification of 3‐hydroxytetradecanoic acid as described by Teixeira et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This constant cycle (higher dietary fat intake and blood LPS) favors the development of chronic metabolic disruptions, like insulin resistance ( 26 ). Recently, Teixeira et al ( 27 ) demonstrated an increased microbial translocation and hyper inflammation in patients with severe COVID-19, provoking higher monocyte activation, which may be associated with worsening outcomes, including death.…”
Section: Ultra-processed Food-based Diet: a Risk Factor For Brain Dys...mentioning
confidence: 99%